Gangguan Mental Emosional Pada Anak Sekolah Dasar - Yonaevy, Umy; Prananingrum, Ratih (Universitas Pahlawan Tuanku Tambusai, 2024)
Mental and emotional disorders experienced by primary school children are a significant problem that requires special attention. The aim of this study was to find the components that contribute to mental emotional disorders in elementary school-aged children. Family environmental factors, genetic factors, and social factors were studied to understand their impact on the mental and emotional state of children. This was done through surveys and data analysis. The study found that environmental, genetic, and social factors are critical to a child's mental health. Another study found that healthy and harmonious family dynamics, sufficient social support, and knowledge of genetic factors can help prevent and overcome mental emotional disorders in elementary school children